Workforce Education: A New Roadmap - Bonvillian, William; Sarma, Sanjay E. (Cambridge, Massachusetts : The MIT Press, 2021)
"Offers a roadmap that will address the gap between the current workforce and the new jobs requiring significant upskilling, with a focus on the sectors of manufacturing, retail, and healthcare."
Keywords: Working class -- United States; Employees -- Training -- United States; Labor market -- United States; Technological innovations -- Economic aspects -- United States